Edukasi Emo-Demo Tablet Tambah Darah dan Peningkatan Pengetahuan Remaja Putri dalam Pencegahan Stunting - Aufa Sofie; Aleyda Najwa; Amanda Aulia; Cahya Dhawiya; Elza Vidyastuti; Lola Azizah; Vania Izdihar; Farida Wahyu Ningtyias (Kolaborasi: Jurnal Pengabdian Masyarakat, 2026)
Introduction: To date, the problem of anemia among adolescents  in Indonesia has not been resolved. This has become a concern for the government because it indirectly contributes to the risk of stunting. In Bondowoso Regency,  the rate of anemia among adolescents continues to increase. This is due to a lack of knowledge about the dangers of anemia and adolescents compliance in taking iron supplements. Objective: This activity aims to increase students understanding of the importance of iron consumption through iron tablets to overcome anemia. Method: This activity was carried out using a combination of the Emo-Demo method and lectures.  The activity was held at SMPN 7 Bondowoso and attended by 44 students on December 7, 2024. The effectiveness of the activity was evaluated by measuring the increase in knowledge about anemia in the form of a post-test knowledge. Results: The pre-test results showed an average of 76,7% correct answers, while the post-test results after the material and Emo-Demo were delivered showed an average of 94% correct answers. There was a 17,3% increase in participants knowledge and understanding.  Conclusion: It can be concluded that Emo-Demo activities with lectures and practice can increase knowledge and understanding.